The effect of cognitive behavioral therapy on the release of interpersonal stress. - Shu, Kunyao (Work, 2021)
BACKGROUND: interpersonal communication in workplace is a problem that is faced by every employee. It is common in all industries and increasingly lethal. When they are unable to bear such overload of psychological pressure, they tend to suffer from anxiety, irritability, depression, and other psychological disorders and even mental diseases. It is urgent to explore how to help employees relieve psychological stress. OBJECTIVE: the study aimed to analyze the effects of cognitive behavioral therapy (CBT) on workplace interpersonal stress, and provide help for professionals, especially newcomers, to relieve social pressure. METHODS: 125 employees of Internet enterprises were given multi-baseline designed CBT (with baseline phase, treatment phase, and post-baseline phase). 43 subjects who did not finish the therapist program were set as the control group and 82 subjects who finished the treatment program were set as the experimental group. First, the differences of interpersonal stress of subjects with different gender, age, educational background, and monthly salary were analyzed. Then, social avoidance, distress, anxiety, and depression scores in baseline, treatment, and post-baseline periods were compared. Finally, the effects of gender, age, educational background, and monthly salary on social avoidance, distress, anxiety, and depression scores of the experimental group were analyzed by multiple regression. and the influence paths of the workplace interpersonal pressure was constructed. RESULTS: Social avoidance, distress, anxiety, and depression of employees earning 10000 or more per month were less than those earning 10000 or more per month. Social avoidance, distress, anxiety, and depression of employees aged 30–50 were higher than those aged < 30 and > 50 (P < 0.05). Social avoidance, social distress, and depression in males were lower than those in females (P < 0.05). Social distress, anxiety, and depression of employees with master's degree or above were less than those with bachelor's degree or junior college degree. There were significant differences between the two groups in the post baseline phase. The monthly salary had the greatest influence on the social avoidance and distress, anxiety, and depression scores of the employees after treatment, with the path coefficients of –0.183, –0.169, and –0.184, respectively. CONCLUSIONS: CBT can effectively relieve social avoidance and distress of workplace employees and can improve the symptoms of anxiety and depression. Educational level, age, and monthly salary had a certain influence on the improvement of social avoidance, distress, anxiety and depression.